A High Result for Image Security Using Crypto-Stegano Based on ECB Mode and LSB Encryption - Kas Raygaputra Ilaga; Christy Atika Sari; Eko Hari Rachmawanto (Universitas Dian Nuswantoro and IndoCEISS, 2018)
The development of the digital world in the field of information technology is so rapid that making the exchange of information easy and fast. Such information may be general or specific. In general information there is no problem for the public, but specific information can not be free in the public. The main problem of the specific information is security, how the information is safe. To overcome these problems can be solved using cryptography and steganography. Cryptography is a technique for securing secret information from uninvolved parties, which the outcome is much different from the original information. Steganography is a technique to secure or hide the secret information on a digital object such as sound, image, vidio that applied results as seen the original information. In this paper proposed a combination of ECB Mode cryptographic method and LSB steganographic method on a digital image. The measurement method are PSNR and MSE to determine the quality of the stego image. Our results are excellent for digital image encryption of RGB and Grayscale type since the resulting image looks like the original image, with the best stego-image proof with MSE is 0.00013, PSNR is 87.00141, SSIM is 1 shown as excellent result.